The Right to Nationality and Repatriation under International Law: A Study on Biharis in Bangladesh - Islam, Mohammed Tahmidul; Mia, Md. Tuhin; Islam, Mazharul (Universitas Negeri Semarang, 2021)
This article aims to examine the legal position of Biharis in Bangladesh and their status in international law. It also reiterates the position of the international community, repatriation rights and judicial decisions on Bihari issues. Despite giving the citizenship rights to the Biharies in Bangladesh many of them did not renounce their Pakistani citizenship and actively refused to integrate with majority Bengalis. Therefore, the Bihari people’s right to get into Pakistan, their homeland, is an internationally recognized right having the force of customary international law. The article is based on secondary data materials. The key sources of this article include textbooks, journal articles, daily newspapers and online documents. The study has also relied on international instruments and decided cases of Apex Court of Bangladesh and Pakistan. The article found that Pakistan has violated and continues to violate the Biharis international right to get into their state of nationality by refusing repatriation. Besides, the new generations of stranded Biharis have mostly rejected their forefather’s stances and ideologies. Hence, the government should give them full opportunity to educate themselves to become productive citizens of Bangladesh.